Collaboration between the Ministry of Education and Culture and the Ministry of Youth and Sports in Successful National Sports Grand Design (DBON) Through Early Identification of Student Talents - Ahmad Muchlisin Natas Pasaribu; Ahmad Budidarma; Satri Dwi Kurnia Nasution (Journal Coaching Education Sports, 2025)
This study aims to map the relationship between certification of Physical Education, Sports and Health (PJOK) educators and the development of students' sports talent in Indonesia, along with the implementation of the National Sports Grand Design (DBON). This study used a descriptive survey method with an instrument in the form of a questionnaire distributed online to 5034 PJOK teacher respondents from a total population of 200,150 teachers throughout Indonesia. The survey results show that there is no clear correlation between the number of certified PJOK teachers and the number of sports talented students. On the contrary, the data also showed that some areas with uncertified PJOK teachers had gifted students. These findings indicate that the certification of physical education teachers does not always affect the quality of sports education in schools, although the presence of certified teachers can improve the management of learning and the development of students' sporting talents. Therefore, there is a need for increased cooperation between the Ministry of Education and Culture and the Ministry of Youth and Sports to create a more holistic and valid data-based sports talent identification system, as well as ensuring equitable distribution of adequate facilities and support to support the development of sports talent in all regions of Indonesia.